2016
DOI: 10.1098/rsta.2015.0426
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hydraulic fracturing: a multi-scale problem

Abstract: Despite the impact that hydraulic fracturing has had on the energy sector, the physical mechanisms that control its efficiency and environmental impacts remain poorly understood in part because the length scales involved range from nanometres to kilometres. We characterize flow and transport in shale formations across and between these scales using integrated computational, theoretical and experimental efforts/methods. At the field scale, we use discrete fracture network modelling to simulate production of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 59 publications
0
60
0
1
Order By: Relevance
“…It has been observed that hydraulic fracturing treatments still leave behind 70-80% of the estimated gas in place [7]. At the early stage of production, the methane in large fractures (hydraulic fracture) and their adjacent natural fracture networks is released quickly, which leads to the rapid initial decline in production [7]. Next, matrix block with high gas exchange rate that depends on the distribution of natural fracture sustains the production at intermediate stage of production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed that hydraulic fracturing treatments still leave behind 70-80% of the estimated gas in place [7]. At the early stage of production, the methane in large fractures (hydraulic fracture) and their adjacent natural fracture networks is released quickly, which leads to the rapid initial decline in production [7]. Next, matrix block with high gas exchange rate that depends on the distribution of natural fracture sustains the production at intermediate stage of production.…”
Section: Resultsmentioning
confidence: 99%
“…However, current extraction efficiency is low. It has been observed that hydraulic fracturing treatments still leave behind 70-80% of the estimated gas in place [7]. At the early stage of production, the methane in large fractures (hydraulic fracture) and their adjacent natural fracture networks is released quickly, which leads to the rapid initial decline in production [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation captures the primary fracture network (outlined in the experiment), as well as bedding plane fractures and densely fractured regions, and illustrates the calculated stress intensity within the specimen. Reproduced from Hyman et al [2].…”
Section: Icc 0000-0001-8531-0531mentioning
confidence: 99%